2021
DOI: 10.1021/acsami.1c18857
|View full text |Cite
|
Sign up to set email alerts
|

A Rationally Designed Supercharged Protein-Enzyme Chimera Self-Assembles In Situ to Yield Bifunctional Composite Textiles

Abstract: Catalytically active materials for the enhancement of personalized protective equipment (PPE) could be advantageous to help alleviate threats posed by neurotoxic organophosphorus compounds (OPs). Accordingly, a chimeric protein comprised of a supercharged green fluorescent protein (scGFP) and phosphotriesterase from Agrobacterium radiobacter (arPTE) was designed to drive the polymer surfactant (S − )-mediated selfassembly of microclusters to produce robust, enzymatically active materials. The chimera scGFP-arP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…The membrane anchor domain (protein fusion 1 ) showed a 10% increase in the radius of gyration ( R g ) upon surfactant conjugation (from 27.4 ± 0.6 to 30.1 ± 0.6 Å), which was accompanied by a 5.5 Å increase (133.5 to 139 Å) in the D max (maximum distance between two atoms), which was calculated from the pair-distance distribution P (r) (Figures b,c and S10). These data indicated that the surfactant electrostatically bound to the anchor domain to form a compact polymer surfactant corona . The Spy-tagged coupling partners CshA-mCh-ST3 (protein fusion 2 ) and mCh-ST3 (protein fusion 3 ) had R g ’s of 58 ± 3 nm and 21.48 ± 0.09 Å and D max values of 239.5 and 95.5 Å, respectively, which demonstrated that the large intrinsically disordered domain of CshA maintained an extended configuration …”
Section: Results and Discussionmentioning
confidence: 90%
“…The membrane anchor domain (protein fusion 1 ) showed a 10% increase in the radius of gyration ( R g ) upon surfactant conjugation (from 27.4 ± 0.6 to 30.1 ± 0.6 Å), which was accompanied by a 5.5 Å increase (133.5 to 139 Å) in the D max (maximum distance between two atoms), which was calculated from the pair-distance distribution P (r) (Figures b,c and S10). These data indicated that the surfactant electrostatically bound to the anchor domain to form a compact polymer surfactant corona . The Spy-tagged coupling partners CshA-mCh-ST3 (protein fusion 2 ) and mCh-ST3 (protein fusion 3 ) had R g ’s of 58 ± 3 nm and 21.48 ± 0.09 Å and D max values of 239.5 and 95.5 Å, respectively, which demonstrated that the large intrinsically disordered domain of CshA maintained an extended configuration …”
Section: Results and Discussionmentioning
confidence: 90%
“…is based that fast and highly effective immobilization, and then isolation and purification of the enzyme itself occurs. The emerging coordination bonds between metal atoms in the carrier and nitrogen atoms in the imidazole rings of the polyhistidine sequence in the protein molecule make it possible to anchor the enzyme on the carrier quite firmly [ 2 , 22 , 23 ] and use it for a long time, in such an immobilized form, for the destruction of OPCs ( Table 1 , [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]). Of particular interest are such immobilization variants for the stabilization and repeated use of the enzyme in the degradation of OPC-polluting water systems [ 22 , 23 ].…”
Section: Stabilization Of Hexa-histidine-containing Oph For Opc Hydro...mentioning
confidence: 99%
“…A fundamentally different approach, based on the use of polyelectrolyte interactions of the surface of the His-tagged enzyme with variously charged surfactants, was used by researchers for the creation of various bioconjugates to improve the stability and catalytic characteristics of the enzyme [ 33 , 34 , 35 ]. At the same time, the expediency of using such coatings for the enzyme, including forming a capsule in the form of a so-called corona, was noted.…”
Section: Stabilization Of Hexa-histidine-containing Oph For Opc Hydro...mentioning
confidence: 99%
See 2 more Smart Citations